Contribution of intestinal lymphatic transport to the antiproliferative effect of delta-9-tetrahydrocannabinol - Wong, Jonathan Chi Man (2017)
Δ9-tetrahydrocannabinol (THC) is the major lipophilic cannabinoid in the cannabis plant and is responsible for many of its pharmacological effects. Cannabis and cannabinoids are often administered orally in foods or lipidic formulations. Marinol® is an oral lipidic formulation containing THC dissolved in sesame oil, and is approved to treat nausea associated with cancer chemotherapy. THC exerts its pharmacological effects by binding to cannabinoid receptors 1 and 2, both of which are involved in a large variety of downstream signalling pathways. Some of these pathways regulate cell death. In agreement with this involvement, THC has been shown to be immunosuppressive in vitro and in vivo. Previous work on synthetic cannabinoids has shown that they can be transported in the lymphatic system in significant amounts when administered orally. The lymphatic system is a passive circulatory network of vessels and lymphocyte-rich nodes that has three major functions. The first function is to maintain body fluid balance. The lymphatic system is open-ended, unidirectional, and collects excess fluid at blood capillaries and tissues. Large molecules that cannot re-enter the blood also enter the lymphatic system. The second function of the lymphatic system is to mount immune responses: after lymphocytes are produced in bone marrow and thymus, they migrate to the lymphatic system and are organised into lymph nodes, which are immunological checkpoints that screen passing fluid for antigens, where innate or adaptive immune responses can be mounted onto them. The third function of the lymphatic system is the absorption of dietary lipids. Lipids are a heterogeneous group of molecules that include lipids, triglycerides and vitamins which are found in food. Lipophilic lipids are emulsified in the gastrointestinal tract by bile and phospholipids, forming mixed micelles. The micelles provide an interface for pancreatic lipase to digest triglycerides into fatty acids and glycerol. These micelles dissociate when they approach the unstirred water layer of the intestinal wall, and the contents are absorbed into specialised enterocytes. Absorption of long-chain fatty acids triggers the production of chylomicrons (CM), a large triglyceride-rich lipoprotein which transports digested fats through the lymphatic system. Triglycerides can then be released from CM by the action of lipoprotein lipase, which is expressed in a variety of cells and tissues. Lipophilic molecules and drugs can associate with CM, and share their fate in the body. Transport through the lymphatic system associated with CM bypasses the liver, which could reduce the first-pass metabolism of a drug. Lipophilic drugs with a high association with CM are prime candidates for lymphatic transport if administered orally. The use of Marinol® by cancer patients receiving chemotherapy could target THC to the lymphatic system, further suppress the immune system of those taking it and possibly making them more vulnerable to secondary infection. Therefore, it is important to confirm whether THC is transported by the intestinal lymphatic system, and whether it is selectively targeted there at immunosuppressive concentrations. To address this research question, analytical assays needed to be developed and optimised to detect THC in a variety of different biological matrices. HPLC-UV methods were successfully developed and validated to determine concentrations of THC in plasma, CM emulsions, and simulated intestinal fluid. The first step to determine the lymphatic transport of THC is to assess the fraction available for absorption in the small intestine. As mentioned previously, Marinol® is a lipidic formulation of THC, and the emulsification and digestion of lipids are not taken into account with traditional drug dissolution techniques. However, an in vitro lipolysis model is a technique that mimics lipid digestion and can reliably predict the absorption of a drug dissolved in a lipidic formulation. After establishment and optimisation of the model, up to 45% of THC dissolved in a lipidic formulation (sesame oil) was solubilised and made readily available for absorption in simulated intestinal fluid. As the concentration of THC in formulation increased, the fraction of drug solubilised decreased. The lymphatic transport potential of THC was then assessed using three techniques – association with CM, pharmacokinetic and biodistribution studies. THC had a high association with CM (72.5%), and its absolute oral bioavailability was improved three-fold when administered in a lipidic formulation (18.5%) compared to a lipid-free formulation (5.73%). At times of peak plasma concentration, the level of THC in mesenteric lymph node homogenate was 30 times higher than plasma, and was at immunosuppressive levels shown in previous in vitro studies (8.6 µg/mL). The mesenteric lymph nodes drain the small intestine, and would be the first nodes that dietary fats pass after being absorbed from the small intestine. Finally, the antiproliferative effect of THC was assessed by exposure to peripheral blood mononuclear cells isolated from healthy individuals and cancer patients recovering from chemotherapy. THC produced a dose-dependent reduction in cell proliferation, with significant differences from vehicle above 10 µg/mL. THC had a reduced effect on cells isolated from cancer patients compared to cells isolated from healthy individuals. THC associated with CM emulsion also had a similarly reduced effect to cells isolated from healthy individuals compared to the effect of THC dissolved in organic solvent. Collectively, this work confirms that THC is transported via the intestinal lymphatic system, and can be concentrated there at extremely high levels, shown to be immunosuppressive in previous in vitro studies.